Modern Imitations and Ancient Inventions: The Battle over Shakespeare's Page - Lupić, Ivan (2010)
The chapter discusses the early phases of eighteenth-century editing of Shakespeare, particularly the work of Alexander Pope and Lewis Theobald. Special attention is paid to the presentation of the text and to the notion of the classic as it was envisioned in the culture of print in England in the seventeenth and eighteenth centuries.